Growth of dropwort plants and their accumulation of bioactive compounds after exposure to UV lamp or LED irradiation - Jeon, Yu-Min; Son, Ki-Ho; Kim, Sang-Min; Oh, Myung-Min (KOREAN SOC HORTICULTURAL SCIENCE, 2018)
High-energy ultraviolet (UV) light is an environmental stress that can be used to stimulate the biosynthesis of bioactive compounds in plants. This study aimed to comparatively determine the effects of UV-A, UV-B, and UV-Clamps or light-emitting diodes (LEDs) on the growth of dropwort (Oenanthe stolonifera) plants, and their contents of bioactive compounds. Dropwort seedlings with 2-3 offshoots were transplanted in a plant factory equipped with white LED and deep flow technique systems, and cultivated under standard growth conditions for 36days. Thereafter, the dropwort plants were supplementally exposed to one of five UV treatments with energy equivalent to 10Wm(-2): UV-C lamps for 2days, UV-B lamps for 3days, and UV-A lamps and LEDs with 370nm or 385nm peak wavelengths for 14days. The variable fluorescence (Fv) to maximum fluorescence (Fm) ratio (Fv/Fm) of dropwort leaves began to significantly decrease 3h after exposure to UV-C, and 6h after UV-B exposure. Fluorescence in UV-C and UV-B-treated plants was lower than in control and UV-A-treated plants during the entire period of UV irradiation. The fresh weight of the shoots of plants treated with UV was not significantly different to those of the control plants during the entire UV irradiation period. The total phenolic content of dropwort shoots exposed to UV-A and UV-B treatments significantly increased compared to that of the control 1day after treatment. The total phenolic content was highest in plants treated with the 370nm UV-A LED, and this was significantly higher (33%) than the control. Plants treated with the 385nm UV-A LED on day 3 of treatment had the highest total phenolic content compared to the other treatments. A similar trend was observed in contents of flavonoids and persicarin. UVlight induced higher anthocyanin content than the control. The activity of phenylalanine ammonia-lyase after UV treatments was significantly higher than the control, supporting the findings of our bioactive compound assays. In conclusion, the results of this study suggest that irradiating vegetables with UV-A LEDs would be useful in plant factories with artificial light for improving vegetable quality without inhibiting growth.
Keywords: ULTRAVIOLET-B RADIATION; OENANTHE-JAVANICA; CHLOROPHYLL FLUORESCENCE; PHENOLIC-COMPOUNDS; PRODUCTION SYSTEM; RESPONSES; LIGHT; PHOTOSYNTHESIS; ANTHOCYANINS; LEAVES